2012
DOI: 10.1007/s00213-012-2843-5
|View full text |Cite
|
Sign up to set email alerts
|

Nonhuman primate models of social behavior and cocaine abuse

Abstract: Rationale Although cocaine is often abused in social situations, very few animal studies examine the effects of cocaine in the context of social behavior. Objectives This review highlights studies investigating the behavioral effects of cocaine in the context of social housing conditions using nonhuman primates. In addition, this review presents recent findings examining the effects of self-administering cocaine on social behavior and the effects of manipulations hypothesized to be stressful or enriching on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 100 publications
3
42
0
Order By: Relevance
“…Studies conducted in rodents (Blanchard et al, 1987; Pohorecky, 2006, 2008) and non-human primates (McKenzie-Quirk and Miczek, 2008) indicate that home-cage ethanol consumption is linked to dominance rank, with the highest rates of consumption in subordinate subjects. Such findings are consistent with the notion that home-cage, free-consumption models may capture the effects of stress induced by social isolation and social hierarchies (for more on the role of social dominance in drug abuse, see review by Nader et al, 2012). …”
Section: Effects Of the Presence Of A Social Peersupporting
confidence: 87%
See 1 more Smart Citation
“…Studies conducted in rodents (Blanchard et al, 1987; Pohorecky, 2006, 2008) and non-human primates (McKenzie-Quirk and Miczek, 2008) indicate that home-cage ethanol consumption is linked to dominance rank, with the highest rates of consumption in subordinate subjects. Such findings are consistent with the notion that home-cage, free-consumption models may capture the effects of stress induced by social isolation and social hierarchies (for more on the role of social dominance in drug abuse, see review by Nader et al, 2012). …”
Section: Effects Of the Presence Of A Social Peersupporting
confidence: 87%
“…Preclinical animal studies have successfully modeled many of these factors and have consistently revealed their role in drug self-administration. For example, studies using rodents and nonhuman primates have revealed that social stress and social isolation increase, whereas social enrichment and social dominance decrease, drug self-administration across a wide variety of drug classes and schedules of reinforcement (see reviews by Burke and Miczek, 2014; Nader et al, 2012; Stairs and Bardo, 2009). That drug use in humans is similarly affected by distal social factors (e.g., Gordon, 2002) supports the validity of these models for predicting human drug use and for evaluating putative interventions for drug use disorders.…”
Section: Introductionmentioning
confidence: 99%
“…buspirone also reported no decreases in cocaine choice. The major finding from this study was that monkeys living in what has been hypothesized to be an enriched environment (Nader et al, 2012a) showed decreases in cocaine choice following acute buspirone administration. As in previous studies Mello et al, 2013), buspirone exhibited behavioral effects that interfered with responding early in the experimental session.…”
Section: Discussionmentioning
confidence: 74%
“…Little is known about the effects of environmental variables on specific D2-like receptor subtypes; it may be that the environmental variables associates with the social hierarchy differentially affect D 2 , D 3 , and D 4 receptors. Considering the well-documented ability of environmentally derived stress and enrichment to modulate cocaine self-administration (see, eg, Nader et al, 2012a;Bardo et al, 2013) the effects of environmental variables on D 3 and D 4 receptors warrant further study.…”
Section: Influence Of Social Rank On the Effects Of Buspironementioning
confidence: 99%
“…Since monkey studies have shown that striatal D2/D3 receptor binding can be changed by environmental factors in social hierarchy [16] (though see [17] suggesting that after differences in D2/D3R binding due to social status have been established, this cannot be changed anymore), future studies in humans investigating whether changes in SES covary with changes in striatal D2/D3R availability are relevant for prevention interventions towards improving health outcomes in individuals who are socially deprived.…”
Section: Discussionmentioning
confidence: 99%